PROSTITUSI TERSELUBUNG (STUDI KASUS TERHADAP PRILAKU AYAM KAMPUS DI KAWASAN KAMPUS PANAM) - Suryani, Ade Irma; ", Yoserizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Covert prostitution undertaken by students or who is often called (Chicken Campus) is considered a deviation by the public. They set a tariff of Rp 2 million to Rp 10 million. These deviations belonging to the secondary aberration, because it has done repeatedly. Users of their services ranging from officials to entrepreneurs both in the city or outside the city of Pekanbaru. This study took place in the District Charming Pekanbaru considering the location is a lot of students. The purpose of this study was to determine the background (chicken Campus) and what are the factors that affect them plunge into the world of prostitution.The method used in this research is descriptive research method. Descriptive research is research that aims to uncover the facts, circumstances, and phenomena. Relation to research by the author is the disclosure of the background (chicken campus) and the factors that influence students into prostitution. Therefore, the author will develop the concept, collecting data and facts that occurred at the sites. The technique of collecting data using in-depth interviews and observation, while data analysis techniques using descriptive qualitative data analysis techniques.Based on the implementation of the research results, namely, the students who work as (chicken campus) have the economic background of the affluent, the majority of students come from families that are less harmonious. Factors that cause them mesuk in prostitution are economic factors, social factors, factors to know a new culture, a lack of social control factor and a factor of friendship.Keywords: Prostitution, Prostitution Covert, Ayam Kampus